P758 Clinical effectiveness of vedolizumab: Interim analysis of the Swedish observational study on vedolizumab assessing effectiveness and healthcare resource utilisation in patients with Crohn's disease (SVEAH CD). (16th January 2018) - Eriksson, C; Rundquist, S; Lykiardopoulos, V; Karlén, P; Grip, O; Söderman, C; Almer, S; Hertervig, E; Gunnarsson, J; Malmgren, C; Delin, J; Strid, H; et al.
Abstract: Background: Clinical trials may not appropriately reflect real-world clinical practice. Therefore, we aimed to assess the clinical effectiveness of vedolizumab in a real-world Crohn's disease (CD) cohort. Methods: This is a prospective, observational, multi-centre cohort study. Eligible patients had active CD confirmed by The presence of ulcers at colonoscopy, contrast enhancement, bowel thickening, or combs sign at magnetic resonance imaging, C-reactive protein (CRP) >upper threshold, Hs-CRP >2.87 mg/l or f-Calprotectin >200 µg/g at initiation of vedolizumab therapy and had started treatment with vedolizumab from 1/6/2015. Exclusion criteria included concurrent participation in a clinical trial in which IBD treatment is dictated by a study protocol and contraindications to vedolizumab. All patients provided a written consent. Data on clinical characteristics, treatment, disease activity and the short health scale (SHS) were recorded at baseline and prospectively, using an electronic Case Record Form, integrated with the Swedish National Quality Registry for IBD (SWIBREG). Data on the patients who had completed the 52 week follow-up are presented. The primary outcome at week 52 was clinical remission, defined as a Harvey Bradshaw Index (HBI) <5. Continuous data are presented as median (interquartile range). Differences between baseline and week 52 were assessed by the Wilcoxon-signed rank test. Results: In total, 169 CD patients had been included by 19/09/2017. Clinical characteristics of patients ( n = 104) who had completed the 52 week study period are shown in Table 1; 95/104 (91%) patients had failed prior anti-TNF therapy. At week 52, 71/104 (68%) were still on treatment with vedolizumab and 45/104 (43%) had achieved clinical remission. Among the 71 patients who had continued vedolizumab treatment, a decrease in the median HBI [6 (3–10) vs. 3 (2–5.5); n = 68; p < 0.001], median CRP [4.0 (2.0–10) g/l vs. 3.0 (1.4–5.0) g/l; n = 67; p = 0.01] and median f-Calprotectin [561 (139.5–830) vs. 232.5 (77.5–464) µg/g; n = 36; p = 0.09] was observed from baseline to week 52. Consistently, quality of life improved, defined by a significant reduction of the overall SHS score ( n = 68; p < 0.001). Conclusions: Vedolizumab treated patients represented a treatment-refractory group. Significant improvements in clinical- and inflammatory activity, as well as in quality of life, were observed in patients who continued treatment through to week 52. The study was financially supported by Takeda.